Legal Aspect in Peace Keeping Operation and Nepal - Giri, Naresh (Unity Journal, 2024)
The United Nations (UN) Charter is the constitution of the UN, that underpins the operational framework of the UN, encompassing the peacekeeping mission to create conditions for lasting peace in conflict-torn countries. Nepal involved in all peace initiatives taken by the UN and largest troop contributor to the UN peacekeeping missions carrying the beacon of peace in the world initiated by Nepal’s enlightened son, Gautam Buddha. This study aims to identify the legal basis of the UN peacekeeping operations implied in the UN Charter and other international law concerning the influence of Buddha’s teaching of peace and non-violence on the global norms of peace. This study also aims to analyze Nepal’s adherence to human rights law and humanitarian law, as well as the legal aspects of Nepal’s participation in UN peacekeeping operations. Methodologically, the study follows a doctrinal approach, focusing on the examination of legal doctrines. The researcher draws upon multilateral conventions, resolutions of the General Assembly and Security Council, decisions of the International Court of Justice, reports, Nepal’s correspondence to the UN, speeches by the Nepali delegation in the UN General Assembly, Nepali laws related to UN peacekeeping, and journal articles as sources of data. This paper argues that as a birthplace of Buddha, Nepal needs to negotiate with the UN to expand its role in securing policy-level and command-level positions in UN peace initiatives, enabling it to contribute more to enhance the legal norms for peacekeeping operations with oriental knowledge of world peace.